Kesalahan Penggunaan Ejaan Bahasa Indonesia Pada Makalah Karya Ilmiah Mahasiswa - Lulu Ilmanun; Rina Devianty (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
The purpose of this research is to analyze the use of Indonesian spelling (EBI) in the papers of students of the Program of Social Sciences Studies of the Islamic State University of North Sumatra. In addition, this article is intended to identify and characterize errors made in the application of EBI in student papers. The aim of this study was to analyze the mistakes students made when using EBI in their papers. This research uses a qualitative descriptive approach. Data collection is done using observation, documentation, and written recording with intralingual and condalingual techniques. The findings indicate that the paper contains many weaknesses in the implementation of the EBI, including spelling errors, improper use of large letters, misuse of prefixes, and misused use of bending letters.